Role of hydrogen bonds and weak non-covalent interactions in the supramolecular assembly of 9-hydroxyeucaliptol: crystal structure, Hirshfeld surface analysis, and DFT calculations - Valle Galvez, Carolina Elizabeth del (2021)
The compound 1,3,3-trimethyl-2-oxabicyclo[2.2.2]octan-9-ol (9-hydroxyeucaliptol) has been prepared and characterized by single-crystal X-ray diffraction analysis, infrared, Raman, and UV-visible spectroscopies. The molecular geometry of the title compound was also investigated theoretically by density functional theory (DFT) calculations to compare with the experimental data. The substance crystallizes in the trigonal crystal system, space group P3₂ with Z = 9 molecules per unit cell. There are three independent molecules in the crystal asymmetric unit having the same chirality and showing some differences in the orientation of the H-atom of the hydroxyl group. The crystal structure of 9-hydroxyeucaliptol shows that the hydroxyl group presents an anti-conformation with respect to the O-atom of the ether group. The crystal packing of 9-hydroxyeucaliptol is stabilized by intermolecular O-H···O hydrogen bonds involving the hydroxyl groups of different molecules, which play a decisive role in the preferred conformation adopted in solid state. The intermolecular interactions observed in solid state were also studied through the Hirshfeld surface analysis and quantum theory of atoms in molecules (QTAIM) approaches. Energy framework calculations have also been carried out to analyze and visualize the topology of the supramolecular assembly, and the results indicate a significant contribution from electrostatic energy over the dispersion.